Precambrian tsunamis in the light of the modern data - D. A. Ruban (Известия высших учебных заведений: Геология и разведка)
Background. In the geological history of the Earth, tsunami events attract particular research attention. Such events are assumed to have taken place already since the Precambrian period. However, the information on Precambrian tsunamis requires systematic generalization.   Aim. To generalize the data published on Precambrian tsunamis with a particular focus on their age, distribution, and possible triggers. The character of information about these natural catastrophes also presents interest.   Materials and methods. A bibliographical review was conducted based on the developed systematization criteria. The information was collected with the Scopus database. A total of 39 sources (articles in the leading scientific journals) were analyzed.   Results. The evidence of tsunami events was obtained for a large part of the Precambrian interval for different regions of the planet. The highest concentrations of the studied catastrophes were established for the end-Early Archean and the Early Proterozoic. Cosmic impacts and earthquakeswere indicated among the triggers. The oldest tsunamis were commonly interpreted by analyzing the composition and textures of rocks. These interpretations frequently proposed no alternative explanations.   Discussion. The available information on Precambrian tsunamis lacks completeness. Two hypotheses were formulated, those assuming the influence of the varied frequency of cosmic impacts and the initiation of lithospheric plate tectonics on the occurrence of tsunamis in the Precambrian.   Conclusion. Previous studies suggest a wide manifestation of tsunami events in the Precambrian. Further research in this direction seems promising, both for Russian and foreign geologists.